2010
DOI: 10.1519/jsc.0b013e3181c7c557
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Static Stretching and Torque Production of the Knee Flexors

Abstract: Recent studies have suggested that acute static stretching (SS) decreases muscular strength and performance, particularly of the knee extensors. The purpose of this study was to investigate the effect of SS on peak concentric and eccentric torque production in the knee flexors. Subjects (13 women and 16 men) were tested for isokinetic concentric (CON) and eccentric (ECC) peak torque at 2 velocities (60 and 210 degrees x s(-1)) before and after a 3-minute knee flexor SS protocol. Subjects also underwent a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 15 publications
2
12
0
4
Order By: Relevance
“…Our study showed that SS at 60 and 300 degrees per second did not affect the PT in the stretched extremity. These findings were in agreement with several previous studies (2,17,26).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study showed that SS at 60 and 300 degrees per second did not affect the PT in the stretched extremity. These findings were in agreement with several previous studies (2,17,26).…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, most studies do not show a negative effect of static stretching on strength performance (2,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Some authors suggest that duration of stretching would certainly have an effect on performance.…”
mentioning
confidence: 99%
“…Thus, dose-dependent effects cannot be examined suitably in this context. Nonetheless, 3 studies (Brandenburg 2006;Sekir et al 2010;Costa et al 2013) reported significant reductions in a total of 8 eccentric strength measures, whereas 6 studies (Ayala et al 2014;Cramer et al 2006Cramer et al , 2007Gohir et al 2012;McHugh and Nesse 2008;Winke et al 2010) reported no change in 15 eccentric measures (≥60 s, -4.2%); these small-tomoderate changes are similar to those observed when isometric and concentric testing were completed (Supplementary Table S4 1 ). Considering that most muscle strain injuries occur during the eccentric phase in most activities (Orchard et al 1997), the limited number of studies describing the effect of SS on maximal eccentric strength is problematic, especially given that no studies have examined the effects of shorter stretch durations.…”
Section: Dose-response Effect For Contraction Typesmentioning
confidence: 79%
“…Many exercises can be used in sports and therapeutic environments for increasing flexibility, enhancing the performance of individuals, and rehabilitating athletes and sedentary people [3,4].…”
Section: Introductionmentioning
confidence: 99%